2003
DOI: 10.1177/104063870301500208
|View full text |Cite
|
Sign up to set email alerts
|

Use of Restriction Fragment Length Polymorphism, Immunoblotting, and Polymerase Chain Reaction in the Differentiation of Avian Poxviruses

Abstract: Abstract. Restriction deoxyribonucleic acid (DNA) fragment profile analysis coupled with immunogenic protein profile analysis has provided useful information in determining the differences between vaccine strains and field isolates of fowlpox virus (FPV). The DNA of strains examined in this study clearly fell into 3 minor groups of restriction patterns similar but distinct from one another: restriction patterns exhibited by the vaccine strains except 1 vaccine strain, Vac-82; restriction profiles indicated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…(2005 ). The presence of poxvirus (Tadese & Reed 2003), the paramyxovirus causing the Newcastle disease (Farkas et al. 2007), the serotypes H5, H7 and H9 of the avian influenza (Kiss et al.…”
Section: Methodsmentioning
confidence: 99%
“…(2005 ). The presence of poxvirus (Tadese & Reed 2003), the paramyxovirus causing the Newcastle disease (Farkas et al. 2007), the serotypes H5, H7 and H9 of the avian influenza (Kiss et al.…”
Section: Methodsmentioning
confidence: 99%
“…in blood was determined as described previously [29,30]. The presence of poxvirus, the paramyxovirus causing Newcastle disease, the serotypes H5, H7 and H9 of avian influenza, falcon adenovirus, circovirus, herpesvirus, polyomavirus, reovirus and West Nile virus were determined following the PCR-based methods available in the literature [31][32][33][34][35][36][37][38][39]. We also searched for helminths and protozoans in the gastrointestinal tract by macroscopic and microscopic observations using standard protocols [40].…”
Section: Methodsmentioning
confidence: 99%
“…To date, most of the identification methods, concerning the APVs are based on PCR and restriction enzyme analysis of 4b gene of pox viruses, a highly conserved in all of Chordopoxvirinae. Differentiation of some APVs has been carried out by using EcoRV and NlaII restriction enzyme profiles on the amplified 4b gene fragment (4). In other study Luschow et al (14) have revealed that restriction digestion of a region between the gene with either MseI or EcoRV enzymes resulted in differentiation of APVs that showed a nucleotide similarity of 72-100%.…”
Section: Discussionmentioning
confidence: 99%
“…Variable restriction enzyme profiles suggest significant genomic differences among avipox viruses (3)(4)(5). Canarypox virus (CPV) is an etiologic agent of canarypox which produces clinical signs including both cutaneous and diptheretic disease forms caused by the prototypical FPV and includes proliferative and necrotic changes in epithelial tissues of the dermis, notably around the eyes and commissures of the beak, feet, and respiratory tract (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%